Evalvacija in samoevalvacija v osnovni šoli - Gosak, Franc; Ivanuš Grmek, Milena; Čagran, Branka (Revija za elementarno izobraževanje, 2016)
Evaluation and Self-Evaluation in Basic School. This article presents the attitude primary education professionals demonstrate towards evaluation and self-evaluation and their actual implementation in schools. In the first part of the article we define the types, aspects and levels of evaluation. We cover the relations between evaluators and the evaluated, as well as factors and results of self-evaluation. The second part of the article presents research results, which reveal that in schools all areas are evaluated to a lesser extent than the professional staff deem them important, and that they mostly express a positive attitude towards evaluation. They see the inspection review as the least important element of school evaluation. Among all education professionals, teachers working in afters-school classes have the least positive attitude towards evaluation.